HUBUNGAN EXPLOSIVE POWER OTOT LENGAN DAN BAHU DAN KOORDINASI MATA-TANGAN DENGAN HASIL SET SHOOT TIM BASKET PUTRA SMA MUHAMMADIYAH 1 PEKANBARU - Fadhila, Mila; Saripin, Saripin; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The Problems in this research starting and observation the author found in the field is. the researchers encountered deficiencies at the time of the shooting in a way set shoot at SMA MUHAMMADIYAH 1 son's basketball team hasn't been satisfying so that Pekanbaru this skill develops better it takes practice and discipline son team basketball SMA MUHAMMADIYAH 1 in doing exercises, in addition to the physical condition also required a skil whether unaccompanied so that achievements can be reached. The research is the research of the correlation. The methods used in this research are methods with test and measurement. This research was conducted against 12 people sample is the basketball team the son SMA MUHAMMADIYAH 1. The tests used in this research is Two-hand Medicine Ball Put which is a test to measure Explosive Power arm and shoulder muscles and throwing a tennis ball catch for eye-hand coordination measure as well as shoot 30 seconds to shoot basketball set of results. The data obtained are statistically analysis, analysis of the data by using a binary correlation analysis. Based on the analysis of the data yields the relationship where there are explosive power arm and shoulder muscles (Xi) and eye-hand coordination (X ') with the result set of the shoot (Y) son of SMA MUHAMMADIYAH 1basketball team in Pekanbaru calculation produces rcount 0,887 > rtable 0,602 there is a relationship of explosive power arm and shoulder muscles (X) and hand-eye coordination (X ') with result set shoot basketball (Y). It can be concluded that Ho was rejected and accepted it shows there is Ha relationship between three variables together.Keywords: Exlosive Power arm and shoulder Muscles, Eye-hand Coordination, the results Set of the shoot Was